2019
DOI: 10.1371/journal.pone.0209909
|View full text |Cite
|
Sign up to set email alerts
|

Machine learning methods for detecting urinary tract infection and analysing daily living activities in people with dementia

Abstract: Dementia is a neurological and cognitive condition that affects millions of people around the world. At any given time in the United Kingdom, 1 in 4 hospital beds are occupied by a person with dementia, while about 22% of these hospital admissions are due to preventable causes. In this paper we discuss using Internet of Things (IoT) technologies and in-home sensory devices in combination with machine learning techniques to monitor health and well-being of people with dementia. This will allow us to provide mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
55
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(63 citation statements)
references
References 45 publications
0
55
0
Order By: Relevance
“…Geriatric patients are also prone to inadequate nutritional intake because of factors, including polypharmacy, decreased mobility, and physiological changes. 15 Often such patients experience deterioration of mental 16 or physical health during their hospital stay, even if they recover from the primary chief of concern for the admission. 17 Studies have also shown that hospitalized geriatric patients have a 60-fold increased risk of developing permanent disabilities 18 making them more susceptible to other adverse ailments.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Geriatric patients are also prone to inadequate nutritional intake because of factors, including polypharmacy, decreased mobility, and physiological changes. 15 Often such patients experience deterioration of mental 16 or physical health during their hospital stay, even if they recover from the primary chief of concern for the admission. 17 Studies have also shown that hospitalized geriatric patients have a 60-fold increased risk of developing permanent disabilities 18 making them more susceptible to other adverse ailments.…”
Section: Introductionmentioning
confidence: 99%
“… 74 Screening tools for dementia are being developed for detecting early cognitive impairments 75–79 and other geriatric health problems such as fall risks 80 and urinary tract infections among patients with dementia. 16 …”
Section: Introductionmentioning
confidence: 99%
“…Second, the system provides the community staff with detailed information regarding each resident’s activities and behavior. Changes in an adult’s activity and behavior are well-characterized to precede health declines; therefore, staff can use this information to quickly identify older adults that are at an increased probability for a health decline and intervene much earlier [ 49 , 50 ]. For example, such information can be used to identify and flag older adults that show the earliest sign of a urinary tract infection (UTI).…”
Section: Discussionmentioning
confidence: 99%
“…For example, such information can be used to identify and flag older adults that show the earliest sign of a urinary tract infection (UTI). In particular, the CarePredict system identifies a new or marked increase in urination urgency or frequency, both well-established indicators for a symptomatic UTI [ 49 - 51 ]. These older adults can then be assessed, and if diagnosed with a UTI, can be provided antibiotics to treat the UTI before it may result in hospitalization [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Emerging evidence supports this approach. A recent study demonstrated the value of home sensing devices for early detection of urinary tract infections in people with dementia [44].…”
Section: Patient and Professional Friendlymentioning
confidence: 99%